2020
DOI: 10.3390/ijms21249338
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Peripheral Biomarkers in Neurodegenerative Diseases: The Tryptophan-Kynurenine Metabolic Pathway

Abstract: Neurodegenerative diseases are multifactorial, initiated by a series of the causative complex which develops into a certain clinical picture. The pathogenesis and disease course vary from patient to patient. Thus, it should be likewise to the treatment. Peripheral biomarkers are to play a central role for tailoring a personalized therapeutic plan for patients who suffered from neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis, among others. Nevertheless, the us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 151 publications
2
86
0
1
Order By: Relevance
“…In recent years, studies of AD, PD and ALS have revealed pathological pathways present in other tissues. Due to some similarities in the peripheral effects in various neurodegenerative disorders, it is worth considering biomarkers which can be used for each of these diseases [ 153 ]. Nevertheless, specific diseases, such as HD, are also characterized by some specific features, which can be analyzed as unique HD biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies of AD, PD and ALS have revealed pathological pathways present in other tissues. Due to some similarities in the peripheral effects in various neurodegenerative disorders, it is worth considering biomarkers which can be used for each of these diseases [ 153 ]. Nevertheless, specific diseases, such as HD, are also characterized by some specific features, which can be analyzed as unique HD biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of this disease has been made to illustrate its general properties. The task is to provide a current landscape, largely common to PD [ 21 , 29 , 36 ] but not always to other neurodegenerative diseases (see, for example, [ 9 , 17 , 28 , 31 , 32 ]).…”
Section: Ad and Its Multiple Fluid Biomarkersmentioning
confidence: 99%
“…Initially, each neurodegenerative disease was considered dependent on a single specific biomarker, such as Aβ for AD and α-synuclein for PD. Now it is clear that these two, as well as many other biomarkers, are not fully specific but expressed also by patients of other neurodegenerative diseases [ 9 ]. Multispecificity of biomarkers requires caution in their operation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the informative biological avenues recently investigated in neuromuscular disorders (NMD), the kynurenine (KYN) Pathway (KP) appears as one of the most promising [ 4 , 5 , 6 ]. KP represents the major route of tryptophan (TRP) catabolism to nicotinamide adenine dinucleotide (NAD+) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%